Genotyping of Methicillin Resistant Staphylococcus aureus Clinical Isolates in Sulaimani City using Pulsed -Field Gel Electrophoresis - Naji, Dunya Emad; Arif, Sehand Kamaluldeen (Tikrit Journal of Pure Science, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) strains cause serious nosocomial infections. The objective of this study was to detect and find the epidemiological relatedness among MRSA isolates which was collected in Emergency burn-and-plastic surgery hospital in Sulaimani city using Pulsed-filed gel electrophoresis (PFGE). Routine methods were used for detection of Staphylococcus aureus, further molecular confirmation was done by PCR assays targeting 16S rRNA gene. The cefoxitin-disc diffusion assay was used for detection MRSA, which is subsequently confirmed by the presence of the mecA gene. PFGE was chosen to observe the genetic relatedness of 10 MRSA strains using SmaI restriction endonuclease. All the isolates (100%, 50/50) carried 16S rRNA gene specific for S.aureus and (42%, 21/50) exhibited resistance to cefoxitin and harboured the mecA gene, thereby being classified as MRSA. Among 10 MRSA isolates, the PFGE pattern were grouped into four clusters. Three isolates belonging to cluster (C3) were indistinguishable, 4 isolates belonging to cluster (C4) were closely related, 2 isolates of the second cluster (C2) were possibly related and the first cluster (C1) with 1 MRSA isolate was unrelated. This finding shows 30% of the samples had indistinguishable fingerprints with no changes in banding profiles, while 40% of the samples had closely related patterns. PFGE is a good discriminatory tool for typing MRSA strains.